PERAMALAN NILAI EKSPOR MIGAS DENGAN MENERAPKAN MODEL AUTOREGREGRESSIVE FRACTIONALLY INTEGRATED MOVING AVERAGE (ARFIMA) - Rahwani, Putri Hazizah; Syaiful, Achmad; Alvionita S, Mika (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Indonesia, a nation in Southeast Asia, has a wealth of natural resources that could serve as the basis for future economic growth. Increased exports of natural resources are crucial for market expansion, job creation, foreign exchange gains, and economic progress. Despite the oil and gas industry's significant contribution, Indonesia still has a trade imbalance in these products and has volatility in export values due to changes in international oil prices and the state of the world economy. This study forecasts the value of Indonesia's oil and gas exports using the Autoregressive Fractionally Integrated Moving Average (ARFIMA) approach, which has a long-term time series structure. The goals of this study are to identify the optimal ARFIMA model using MAPE and AIC for data on oil and gas export values, forecast the value of oil and gas exports using the optimal ARFIMA model many months in advance, and assess the ARFIMA model's forecasting accuracy. The best model, according to the results, is ARFIMA (0, [0.32], 2), with a MAPE score of 1.78%, indicating strong predicting accuracy for the upcoming periods. It is anticipated that this model will support Indonesia's economic stability and aid the government in strategic planning.